Industry Support Institutions Fostering Innovations Culture among SMEâ€™s of Punjab, India: A Strategic Perspective - Sangha, B.S.; Singh, T.P.; Batish, Ajay (The Asian Journal of Technology Management (AJTM), 2013)
. The present paper attempts to investigate the role of six Industry Support Institutions in fostering innovation culture in manufacturing sector of Punjab in India. Some path breaking technological innovations have been introduced by the Institutions. These highly interactive, self-reliant institutes are the virtual In-house R&D to SMEs. Knowledge accumulations in the institutes also offer a platform for exchange of ideas which further facilitate the process of open innovation. The speedy and efficient dissemination of technical know-how by these institutes have brought creativity and innovativeness among SMEs of the region. Â Keywords: Industry Support Institutions, Open Innovation, Small and Medium Enterprises.